The Effect of Buerger Allen Exercise on Perfusion of Peripheral Tissues in Patients with Diabetes Mellitus: Literature Reviews - Anggraeni, Hani Nur; Vitaliati, Trisna; Cahyono, Hendra Dwi (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Diabetes mellitus is not treated immediately can cause ineffective peripheral tissue perfusion. Ineffective peripheral tissue perfusion can lead to lower extremity amputation. Buerger allen exercise can improve ineffective peripheral tissue perfusion with an indicator of increasing the value of the ankle brachial index (ABI). This literature study aims to explore the intervention of Buerger Allen exercise on the ineffectiveness of peripheral tissue perfusion in patients with diabetes mellitus. This study uses a literature review method with 3 databases, namely Proquest, Google Scholar, and PubMed with a total of 6 articles reviewed with the PICOS framework criteria. The criteria for the articles used are those published from 2016 to 2021 amounting to 2,445 articles, then a selection is made based on duplicate titles, PICOS and critical appraisal to 6 articles. The administration of Buerger Allen exercise greatly affects the increase in the value of the ankle brachial index (ABI) as an indicator of the effectiveness of peripheral tissue perfusion in patients with diabetes mellitus. All reviewed articles show the same results. Buerger allen exercise can increase oxygen in the blood vessels so that it can be an alternative therapy that can be given to people with diabetes mellitus to improve ineffective peripheral tissue perfusion.